Interpretive structural modeling of factors affecting the internal development of cities in arid regions (Case study: Ardakan city - mohamad reza hatafi ardakani; mphammad hosein saraei; mohamad mahdi karimnejad; seyed ali almodaresi; saideh moayed far (تحقیقات کاربردی علوم جغرافیایی)
One of the aspects of sustainable urban development and balanced physical development is in line with ecological and socio-economic environmental conditions. In the last decades of the twentieth century, despite many efforts in the field of sustainable spatial development of cities, this issue still remains an important challenge for geographers, urban planners, architects and urban planners. In many cities in developing countries, rapid urbanization and increasing urban population have exacerbated environmental hazards. This is doubly important in small cities. Because physical development, in addition to land use change, has met the basic needs of urban society, including the provision of safe and sufficient water, green space per capita, urban waste management and environmental pollution. The present study is applied in terms of purpose and analytical in terms of method. The statistical population consisted of university professors and experts in the field of research in Ardakan who were selected by purposive sampling. They were selected to conduct and implement the research. In order to achieve the research objectives, using a new analytical methodology of interpretive structural modeling (ISM), the relationships between the factors were determined and analyzed in an integrated manner. Finally, using MICMAC analysis, the factors were analyzed according to the impact and effectiveness on other components. The results of the interpretive structural model of the factors affecting the inner development of the city showed that the obtained model includes three levels and the results showed that the managerial and physical factors are the most basic factors affecting the inner development of the city that should be addressed in the first place. In other words, any action to pave the way for the internal development of the city, requires attention to these factors along with other factors